Smoke Precipitation by Exposure to Dual-Frequency Ultrasonic Oscillations - Vladimir Khmelev; Andrey Shalunov; Sergey Tsyganok; Pavel Danilov (Fire)
The analysis conducted herein has shown that the efficiency of smoke precipitation can be improved by additionally making smoke particles interact with ultrasonic (US) oscillations. Because the efficiency of US coagulation lowers when small particles assemble into agglomerates, the authors of this work have suggested studying how smoke particles interact with complex sound fields. The fields are formed by at least two US transducers which work at a similar frequency or on frequencies with small deviations. To form these fields, high-efficiency bending wave ultrasonic transducers have been developed and suggested. It has been shown that a complex ultrasonic field significantly enhances smoke precipitation. The field in question was constructed by simultaneously emitting 22 kHz US oscillations with a sound pressure level no lower than 140 dB at a distance of 1 m. The difference in US oscillations’ frequencies was no more than 300 Hz. Due to the effect of multi-frequency ultrasonic oscillations induced in the experimental smoke chamber, it was possible to provide a transmissivity value of 0.8 at a distance of 1 m from the transducers and 0.9 at a distance of 2 m. Thus, the uniform visibility improvement and complete suppression of incoming smoke was achieved. At the same time, the dual-frequency effect does not require an increase in ultrasonic energy for smoke due to the agglomeration of small particles under the influence of high-frequency ultrasonic vibrations and the further aggregation of the formed agglomerates by creating conditions for the additional rotational movement of the agglomerates due to low-frequency vibrations.